Aerosol generation during chest compression and defibrillation in a swine cardiac arrest model. (February 2021) - Hsu, Cindy H.; Tiba, Mohamad H.; Boehman, André L.; McCracken, Brendan M.; Leander, Danielle C.; Francalancia, Stephanie C.; Pickell, Zachary; Sanderson, Thomas H.; Ward, Kevin R.; Neumar, Robert W.
Abstract: Aim: It remains unclear whether cardiac arrest (CA) resuscitation generates aerosols that can transmit respiratory pathogens. We hypothesize that chest compression and defibrillation generate aerosols that could contain the SARS-CoV-2 virus in a swine CA model. Methods: To simulate witnessed CA with bystander-initiated cardiopulmonary resuscitation, 3 female non-intubated swine underwent 4 min of ventricular fibrillation without chest compression or defibrillation (no-flow) followed by ten 2-min cycles of mechanical chest compression and defibrillation without ventilation. The diameter (0.3–10 μm) and quantity of aerosols generated during 45-s intervals of no-flow and chest compression before and after defibrillation were analyzed by a particle analyzer. Aerosols generated from the coughs of 4 healthy human subjects were also compared to aerosols generated by swine. Results: There was no significant difference between the total aerosols generated during chest compression before defibrillation compared to no-flow. In contrast, chest compression after defibrillation generated significantly more aerosols than chest compression before defibrillation or no-flow (72.4 ± 41.6 × 10 4 vs 12.3 ± 8.3 × 10 4 vs 10.5 ± 11.2 × 10 4 ; p < 0.05), with a shift in particle size toward larger aerosols. Two consecutive human coughs generated 54.7 ± 33.9 × 10 4 aerosols with a size distribution smaller than post-defibrillation chest compression. Conclusions: Chest compressions alone did not cause significant aerosol generation in this swine model. However, increased aerosol generation was detected during chest compression immediately following defibrillation. Additional research is needed to elucidate the clinical significance and mechanisms by which aerosol generation during chest compression is modified by defibrillation.